Use of RICE research outputs in the formulation of the The Philippines Rice Industry Roadmap 2030 - CGIAR Research Program on Rice (2018)
The Philippines Rice Industry Roadmap 2030 (PRIR 2030) draws heavily from the research output of the “Benchmarking the Philippine Rice Economy Relative to Major Rice Producing Countries in Asia”, a collaborative project of IRRI and PhilRice funded by the Philippine Department of Agriculture